Insight into Reduction Process of Diquat on Silver and Copper Electrodes Studied Using SERS - María Rosa López-Ramírez; Lucas Olivares-Fernández; Santiago Sanchez-Cortes (Chemosensors)
A surface-enhanced Raman scattering (SERS) study of diquat (DQ) on silver and copper electrodes is presented in this work in order to complete previous studies on the SERS of DQ on metal nanoparticles. We supported the experimental results with theoretical calculations of different species of DQ, analyzing the most important molecular differences and their corresponding Raman spectra. DQ SERS spectra on Ag and Cu electrodes were obtained at different excitation wavelengths. An analysis of the SERS spectra revealed that at more positive electrode potentials, the interaction of DQ with the metal formed a charge-transfer complex via the chloride anion previously adsorbed on the surface; additionally, at more negative potentials, other species of diquat, such as DQ2+, could be directly adsorbed on the metal’s surface. Finally, we detected new SERS bands corresponding to DQ at negative electrode potentials that were sensitive to the excitation wavelength, suggesting that lateral interactions between radical cation species on the electrode surface lead to intramolecular dimerization and a possible multilayer of the adsorbate.